Summary of the HESI Consortium Studies Exploring Circulating Inhibin B as a Potential Biomarker of Testis Damage in the Rat. (30th January 2013) - Chapin, Robert; Weinbauer, Gerhard; Thibodeau, Michael S.; Sonee, Manisha; Saldutti, Louise Parks; Reagan, William J.; Potter, David; Moffit, Jeffrey S.; Laffan, Susan; Kim, James H.; Goldstein, Richard A.; Erdos, Zoltan; et al.
<x xml:space="preserve">Abstract</x> The Developmental and Reproductive Toxicity Technical Committee of the Health and Environmental Sciences Institute hosted a working consortium of companies to evaluate a new commercially available analytic assay for Inhibin B in rat serum or plasma. After demonstrating that the kit was stable and robust, the group performed a series of independent pathogenesis studies (23 different compound/investigator combinations) designed to examine the correlation between the appearance of lesions in the testis and changes in circulating levels of Inhibin B. These studies were reported individually in the previous articles in this series (this issue), and are discussed in this paper. For roughly half of these exposures, lesions appeared well before Inhibin B changed. A few of the studies showed a good correlation between seminiferous tubule damage and reduced circulating Inhibin B levels, while for seven exposures, circulating Inhibin B was reduced with no detectable alteration in testis histology. Whether this indicates a prodromal response or a false‐positive signal will require further investigation. These exceptions could plausibly suggest some value of circulating Inhibin B as a useful biomarker in some circumstances. However, for roughly half of these exposures, Inhibin B appeared to be a lagging biomarker, requiring significant damage to the seminiferous tubules before a consistent and credible reduction in circulating levels of Inhibin B was observed.